Novel and emerging therapies in pulmonary arterial hypertension - Cassady, Steven J.; Soldin, Danielle; Ramani, Gautam V. (Frontiers in Drug Discovery, 2022)
Pulmonary arterial hypertension (PAH), defined as a mean pulmonary artery pressure exceeding 20 mmHg with a pulmonary vascular resistance of 3 or more Wood units, is an incurable and progressive condition. The cornerstone of PAH treatment is pulmonary vasodilators, which act on the pulmonary vasculature to reduce pulmonary pressures and pulmonary vascular resistance and prevent progression to right heart failure. The number of available pulmonary vasodilator therapies has grown markedly in the last 10 years, alongside a rapidly expanding body of literature establishing strategies for their use. Up-front combination therapy, typically with two pulmonary vasodilator medications, has become the standard of care based on landmark trials showing superior outcomes over single therapies alone. Complex risk stratification matrices have begun to see widespread use as tools with which to guide changes in PAH therapies for individual patients. Strategies for using the pulmonary vasodilators in common use continue to be evaluated in trials exploring concepts such as up-front triple combination therapy and substitution of vasodilators for patients not meeting therapeutic goals. Alongside established pulmonary vasodilator therapies for PAH, there is a broad spectrum of experimental therapies that are being studied for the disease. These include both more conventional medications that act on pathways targeted by existing vasodilator therapies as well as non-vasodilator treatments with novel methods of action, that may act both to vasodilate and to address the detrimental changes of pulmonary arterial and right ventricular remodeling. Many of these emerging medications are the focus of active phase 2 and 3 trials. Finally, there has been significant interest in therapeutic pathways that are well established in left heart failure, with the hope of adapting strategies that may be efficacious in PAH and right heart failure as well. These include explorations of pathways treated by goal-directed medical therapy as well as device therapies such as pacing, resynchronization therapy, and cardiac monitoring devices. Many of these options show promise and may represent a complementary approach to treatment of PAH, allowing for multimodal therapy alongside pulmonary vasodilators to improve patient outcomes.